2008
DOI: 10.1111/j.1440-1827.2008.02223.x
|View full text |Cite
|
Sign up to set email alerts
|

Dinucleotide repeat polymorphisms of RAD51, BRCA1, BRCA2 gene regions in breast cancer

Abstract: Recent studies suggest that genetic polymorphisms of the DNA repair genes have been implicated in breast cancer risk. BRCA1 and BRCA2, two breast cancer susceptibility genes, are essential to maintain chromosomal integrity. This is mediated via regulation of RAD51 during homologous recombination. Dinucleotide polymorphism repeats in the 15q14-21, 17q21 and 13q12-13 regions, where the RAD51, BRCA1 and BRCA2 genes are located, respectively, have been evaluated. The polymorphism was determined using the following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…But further studies will be reveal relation of this mutation with breast cancer. In confirmation of this study, allele variation in STR marker in RAD51 gene associated with breast cancer (Nowacka-Zawisza et al, 2008). Also, in other studies, researchers have been found alternative haplotype association with various cancer (Huang et al, 2007;Ozolina et al, 2009;Panczyk et al, 2009).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…But further studies will be reveal relation of this mutation with breast cancer. In confirmation of this study, allele variation in STR marker in RAD51 gene associated with breast cancer (Nowacka-Zawisza et al, 2008). Also, in other studies, researchers have been found alternative haplotype association with various cancer (Huang et al, 2007;Ozolina et al, 2009;Panczyk et al, 2009).…”
Section: Discussionsupporting
confidence: 84%
“…Several mutations have been reported associated with breast cancer in Iranian patients (Desantis et al, 2014;Forat-yazdi et al, 2015). In some disease, intragenic marker polymorphism be used as an explorer tool for finding patients carrying mutation (Ali et al, 2007;Miresmaeili et al, 2016;Nowacka-Zawisza et al, 2008;Osorio et al, 2003). STR markers of a gene are good evidence for following of mutation in a family or population.…”
Section: A Novel Mutation-brca1 Associated Hereditary Haplotype Of Inmentioning
confidence: 99%
“…Interestingly, the 5301insA mutation falls in exon 11 of the BRCA2 gene, which is known as the ovarian cancer cluster region (OCCR). Tandemly repeated sequences may lead to instability in maintaining chromosomal integrity, thus ultimately allowing for a mutational hotspot to occur (11). The families in the study were either ascertained through population-based studies of patients with either breast or ovarian cancer, or on the basis of the presence of at least two relatives with either breast or ovarian cancer and at least one family member tested positive for a deleterious BRCA2 mutation.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that this mutation arose due to its occurrence in this hotspot region of the gene. Tandemly repeated sequences may lead to instability in maintaining chromosomal integrity, thus ultimately allowing for a mutational hotspot to occur (11).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that lymphocytes of breast cancer patients are characterized by an enhanced in vitro chromosomal radiosensitivity (Jones et al 1995;Scott et al 1998Scott et al , 1999Baeyens et al 2002Baeyens et al , 2005, suggests that breast cancer can be driven by DSB-initiated chromosomal instability. This hypothesis is further supported by the involvement of BRCA1 and BRCA2 in DSB repair (Tutt and Ashworth 2002) and by several populationbased case-control studies, showing a link between single nucleotide polymorphisms (SNPs) in DSB repair genes and breast cancer risk (Dunning et al 1999;Kuschel et al 2002;Fu et al 2003;Bau et al 2004Bau et al , 2007Zhang et al 2006;Ralhan et al 2007;Nowacka-Zawiszac et al 2008;Willems et al 2008). Repair of DSBs in mammalian cells occurs by two main pathways, homologous recombination (HR) and non-homologous end-joining (NHEJ) (reviewed in Valerie and Povirk 2003).…”
Section: Introductionmentioning
confidence: 95%